Homogeneização numérica para a avaliação da resistência mecânica de materiais porosos com matriz de von Mises e poros esferoidais - Knob, Juliano Hertz (2024)
This work analyzes the influence of porosity and pore shape on the mechanical strength of ductile materials, applying computational homogenization to an elementary volume with a single pore using the finite element method. The study details the impact of volumetric fraction and aspect ratio of elongated (prolate) pores on the effective yield stress of porous materials with a von Mises matrix. Different loading conditions are considered, varying the triaxiality of macroscopic stress. For this purpose, boundary conditions in terms of displacements are imposed using user routines (Multi-point constraint, MPC), such that the stress triaxiality remains constant during loading. As a result, numerical effective yield surfaces are obtained that demonstrate the effects of porosity and pore geometry on the mechanical strength of porous materials in the analyzed context. The results indicate that both the level of porosity and the shape of the pores significantly reduce the mechanical strength of the material, which could have implications for the development and optimization of new materials and processes in engineering. The study advances the understanding of porous materials, providing a solid foundation for future investigations, especially regarding the modeling of the yield surface, which plays a crucial role in predicting mechanical behavior under different loading conditions.